Polynomial algebra reveals diverging roles of the unfolded protein response in endothelial cells during ischemia–reperfusion injury. Issue 17 (16th June 2014) - Le Pape, Sylvain; Dimitrova, Elena; Hannaert, Patrick; Konovalov, Alexander; Volmer, Romain; Ron, David; Thuillier, Raphaël; Hauet, Thierry
Abstract : The unfolded protein response (UPR) – the endoplasmic reticulum stress response – is found in various pathologies including ischemia–reperfusion injury (IRI). However, its role during IRI is still unclear. Here, by combining two different bioinformatical methods – a method based on ordinary differential equations (Time Series Network Inference) and an algebraic method (probabilistic polynomial dynamical systems) – we identified the IRE1α–XBP1 and the ATF6 pathways as the main UPR effectors involved in cell's adaptation to IRI. We validated these findings experimentally by assessing the impact of their knock‐out and knock‐down on cell survival during IRI. Abstract : A new application of recent bioinformatical methods is proposed. It determines the most dysregulated genes and the most disruptive genes in response to a stimulus. The method is tested in the context of ischemia–reperfusion. It identifies the involvement of two pathways of the unfolded protein response. The predictions are confirmed experimentally with two different cell types.